Involvement of liver kinase B1 in the ameliorative action of epigallocatechin-3-gallate against MAFLD progression in mice - Mahardian Rahmadi; Chia-Wei Phan; Santhra Segaran Balan; Athallah Syauqi Zumarthana; Ellyna Majesty Ayundari; Ismailia Wienda Yasmin Pratama Putri; Salsabila; Ahmad Dzulfikri Nurhan (Pharmacia)
Metabolic dysfunction-associated fatty liver disease (MAFLD) is characterized by intrahepatic fat accumulation in individuals without a history of excessive alcohol consumption. This study investigated the effects of epigallocatechin-3-gallate (EGCG) on reducing MAFLD severity. Twenty-four ddY mice were divided into three groups: normal feed, high-fat diet (HFD), and HFD + 25 mg/kg EGCG supplementation. All mice were provided with food and water ad libitum; the remaining feed and body weight were measured daily for 28 days. On the 15th day, the therapy group received EGCG intraperitoneally. At the end of the study, mice were sacrificed, and their livers were collected for histopathological examination and measurement of LKB1, CD86, and CD163 mRNA expression. The results indicated that LKB1 expression increased significantly following EGCG administration. Additionally, histopathological analysis revealed a positive impact of EGCG on hepatocyte repair. In conclusion, the 14-day EGCG treatment demonstrated promising results in improving liver health in mice with MAFLD and modulating LKB1 expression.